Experimental Study on Operational Stability of Centrifugal Pumps of Varying Impeller Types Based on External Characteristic, Pressure Pulsation and Vibration Characteristic Tests - Jia, XiaoQi; Chu, Qingyang; Zhang, Li; Zhu, ZuChao (Frontiers in Energy Research, 2022)
This study performed external characteristics, dynamic pressure, and vibration tests on the closed impeller model, semi-open type impeller model, and open impeller model in order to study the influence of the impeller structure on the operational stability of the pump. According to the research findings, the external characteristics of the three impellers enjoyed favorable stability with flat curves under low flow rates. As the flow increases, the stability of the external characteristics weakens, and the poorest stability can be observed in the open impeller, while the enclosed impeller has the best stability under a large flow rate. In addition, intense pressure fluctuations arise near the casing tongue due to the dynamic and static interference between the blade and the casing tongue, causing a large amplitude of pressure pulsation near the casing tongue and the pump outlet. It can be seen that the stability of pressure pulsation of the closed impeller in the casing tongue area was the best, whereas the stability of pressure pulsation of the open impeller was the poorest. The minimum casing vibration can be found in the closed impeller, followed by the semi-open impeller, and the open impeller, with the maximum vibration. In addition, the optimum stability of rotor vibration can be observed in the closed impeller, semi-open impeller, and open impeller with similar stability of rotor vibration.